Гомогендерні проблеми у сучасному суспільстві - Головко, І. О. (ХНУРЭ, 2012)
Problem of sexual orientation has always attracted the attention of various social institutions. It's no secret that homophobia trends in the Ukrainian society is still quite common, although they relate more gay men than lesbians